A Study to Assess the Level of Job Satisfaction and Quality of Marital Life among Staff Nurses Working in Shift Duties in a View to Develop a Booklet in Selected Hospitals of Jabalpur - Shrivas Verma, Gayatri (International Journal of Nursing and Medical Investigation, 2024)
Aim: The purpose of this study is to assess the level of job satisfaction and quality of marital life among staff nurses working in shift duties in a view to develop a booklet in selected hospitals of Jabalpur. Materials and Methods: The study involved Jabalpur’s Netaji Subhash Chand Bose Medical College and Hospital and Victoria’s Seth Govind Das district hospital staff nurses. A non-probability convenient sample of 100 staff nurses was chosen. Results: Staff nurses are 91% female and 9% male, with 46% aged 21–30 and 6% over 51. Arranged marriages 63%, love 18%. Nuclear families represent 46% and joint families 54%. 43% were married <5 years and 14% for over 15. About 40% of staff nurses have children, 22% did not. Compared to 9% of rural areas, 81% of staff nurses’ dwellings are residential. About 72% of staff nurses had diplomas and 2% had M.Sc. Staff nurse spouses were 70% government workers and 7% entrepreneurs. Staff nurses stated 4% had a family history of mental illness and 94% did not. A family history of drug or alcohol abuse showed that 8% of staff nurses were dependent and 92% were not. About 95% are middle, and 2% are low. Staff nurse contentment. Job satisfaction was 97% good for staff nurses and 0% low. Standard deviation: 3.98, mean job satisfaction: 39. Staff nurses’ marriage norm. About 13% of staff nurses were happy, and 42% were not. Conclusion: Job satisfaction among staff nurses was most strongly connected with years after marriage, number of children, monthly salary, and clinical experience, with a family history of mental illness being significantly lower. Sociodemographic factors did not affect job satisfaction. Many sociodemographic factors mattered. Demographical factors connected with job satisfaction and married life quality among Jabalpur hospital staff nurses.